Influence of Sex-Mismatch on Prognosis After Heart Transplantation - Ayesta, Ana (Frontiers in Cardiovascular Medicine, 2021)
The influence of donor and recipient sex on prognosis after heart transplantation has been analyzed in single, multi-center studies and international registries. In most of them, sex mismatch was identified as a risk factor for the worst prognosis, especially in men recipients of female heart. This could be attributed to physiological differences between women and men, differences in complications rates after heart transplantation (rejection, cardiovascular allograft vasculopathy, and primary graft failure), and pulmonary hypertension of the recipient. Confounding variables as age, urgent transplantation, and size mismatch should also be considered. When allocating a graft, sex mismatch should be considered but its influence in long-term survival should be further explored.